Sekule, Slowakei. Ein germanisches Gräberfeld an der March - Hüssen, Claus-Michael; Rajtár, Ján; Voß, Hans-Ulrich (e-Forschungsberichte des DAI, 2017)
Within the framework of the German-Slovakian project to explore the Roman presence north of the Pannonian frontier on the Danube and the interaction with the native population beyond, the Germanic burial ground field in Sekule was examined. The site is located west of the Little Carpathians on the left side of the March. In four campaigns from 2012 to 2015, 36 burials from the later 1st century to the beginning of the 3rd century AD were studied. The majority of the dead were buried in the second half of the 2nd century AD. Almost all graves were equipped with Roman vessels made of bronze or ceramics. Together with the weapons in the men‘s tombs and the parts of the costume in the graves of the women, the connections between the Germanic population living in the lower Morava valley and the Roman Empire as well as far into the Germanic regions in the north are shown.